How do idiosyncratic deals contribute to the employability of older workers?. Issue 2 (9th May 2016) - Oostrom, Janneke K.; Pennings, Martine; Bal, P. Matthijs
Abstract : Purpose: – The purpose of this paper is to examine the relationships of i-deals with the employability of older workers, and introduce two distinct theoretical processes through which these effects occur. On the one hand, a self-enhancement perspective postulates that i-deals enhance self-efficacy through which older workers become more employable. On the other hand, a lifespan perspective postulates that i-deals enhance older workers' future time perspective through which they become more employable. Design/methodology/approach: – Data were gathered among 244 employees via an online questionnaire that had been sent to employees of 45 years or older at eight companies in the Netherlands. Findings: – Results showed that task and work responsibilities i-deals are strongly related to older workers' employability, and that this relationship is mediated by future time perspective and self-efficacy. Location flexibility i-deals were positively related to employability. Financial i-deals and schedule flexibility i-deals were unrelated to employability. Research limitations/implications: – This study introduces two novel ways through which i-deals for older workers can be studied: a self-enhancement and a future time perspective. Both can explain how older workers may enhance their employability by negotiating i-deals. Practical implications: – As the percentage of older workers will increase, there is a great need for organizations to focus on the employability of older workers. The present study shows that organizations are able to increase the employability of older workers by individual arrangements. Originality/value: – Individualization of work arrangements has been theorized to facilitate older workers' employability, but the present study is the first to investigate how i-deals may contribute to greater employability.